2022
DOI: 10.3390/biomedicines10082016
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cardiogenic Edema with Sodium–Glucose Cotransporter-2 Inhibitors in Heart Failure with Reduced Ejection Fraction: Mechanisms and Insights from Pre-Clinical Studies

Abstract: In heart failure with reduced ejection fraction (HFrEF), cardiogenic edema develops from impaired cardiac function, pathological remodeling, chronic inflammation, endothelial dysfunction, neurohormonal activation, and altered nitric oxide-related pathways. Pre-clinical HFrEF studies have shown that treatment with sodium–glucose cotransporter-2 inhibitors (SGLT-2i) stimulates natriuretic and osmotic/diuretic effects, improves overall cardiac function, attenuates maladaptive cardiac remodeling, and reduces chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…The diuretic/natriuretic properties of SGLT2 inhibitors may offer benefits in reducing congestion and may allow a reduction in loop diuretic requirement [2,80]. HFrEF pre-clinical studies have shown that SGLT2 inhibitors treatment may attenuate edema formation not only through the stimulation of natriuretic and osmotic/diuretic effects, but also through improvement in overall cardiac function, and the suppression of maladaptive cardiac remodeling, chronic inflammation, oxidative stress, and endothelial dysfunction [81]. Clinical HFrEF studies also suggest that SGLT-2 inhibitors treatment may attenuate the pathological salt-water retention [82].…”
Section: Sodium-glucose Co-transporter 2 Inhibitors (Sglt2 Inhibitors)mentioning
confidence: 99%
“…The diuretic/natriuretic properties of SGLT2 inhibitors may offer benefits in reducing congestion and may allow a reduction in loop diuretic requirement [2,80]. HFrEF pre-clinical studies have shown that SGLT2 inhibitors treatment may attenuate edema formation not only through the stimulation of natriuretic and osmotic/diuretic effects, but also through improvement in overall cardiac function, and the suppression of maladaptive cardiac remodeling, chronic inflammation, oxidative stress, and endothelial dysfunction [81]. Clinical HFrEF studies also suggest that SGLT-2 inhibitors treatment may attenuate the pathological salt-water retention [82].…”
Section: Sodium-glucose Co-transporter 2 Inhibitors (Sglt2 Inhibitors)mentioning
confidence: 99%
“…The decongestive power of SGLT2i has been studied in acute settings [ 10 , 11 ]. SGLT2i, in fact, may indirectly slow edema development with different mechanisms, such as improvement of the stroke volume and reduction of inflammation and endothelial dysfunction, as is further discussed [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of modern treatments, for instance sacubitril/valsartan and sodium-glucose co-transporter-2 inhibitors ( 5 , 6 ), in clinical practice is required to improve management of congestion and, importantly, long term outcomes in patients with HFrEF. However, further research is needed to develop affordable methods and strategies that combine biomarkers, imaging modalities and other diagnostic tools to detect, quantify and monitor edema due to cardiac dysfunction timely and with precision ( Figure 1 ).…”
mentioning
confidence: 99%